Pandemic in the Flint Hills - Patrick Kirk (Symphony in the Flint Hills, 2013)
In 1918 during the last months of the First World War, Spanish influenza progressed from a relatively mild flu into a deadly, worldwide epidemic - a pandemic.
Keywords: Spanish influenza; flu; pandemic; hospital; epidemic; Kansas State Agricultural College; students; school; bacterium; Pfeiffer& #x27; s bacillus; Student Army Training Corps; Camp Funston; Kansas Health Department; Fort Riley; doctors; sanitary; Germany; First World War; meningitis